Co-positioning design for sustainability transitions, practice theory and transitions theories: towards dialogue and collaboration. (5th July 2021) - Öztekin, Elif Erdoğan; Gaziulusoy, İdil
This paper examines the integration potential of three bodies of knowledge that theorise and strategise about sustainability transitions and societal change: design for sustainability transitions (DfST), transitions theories (TTs) and practice theory (PT). After presenting an overview of their particular conceptions of change, narratives of change and foci of interventions, we comparatively assess: i) the dynamics of societal change that they highlight; ii) the scopes of change that they target and iii) the phases of change with which they actively engage. Our findings suggest that DfST, TTs and PT undertake distinct and yet equally relevant and necessary lenses and practices to understand and steer sustainability transitions. We argue that there is a need for establishing dialogues and collaborations between these three approaches, linking their activities, processes, learnings and propositions in order to initiate the formation of an aligned sustainability transitions research.